Preparation of supported AuPd nanoalloys mediated by ionic liquid-like functionalized SBA-15: structural correlations concerning its catalytic activity. (1st June 2016) - Damasceno, João Paulo Vita; Maroneze, Camila Marchetti; Strauss, Mathias; Sigoli, Fernando Aparecido; Mazali, Italo Odone
Abstract : We report highly active catalysts based on mono- or bimetallic Au and Pd nanoparticles supported in ionic liquid-like modified SBA-15. Abstract : Noble metal nanoalloys are very important in catalysis, sensing, electrochemistry, and plasmonics. Based on the importance of these materials and in order to overcome the synthetic limitations for the in situ synthesis of supported nanoalloys in porous supports, we extended a synthetic protocol to achieve supported AuPd nanoalloys within SBA-15 pores modified with an ionic liquid-like alkoxysilane. The synthesized materials form very small nanoparticles with non-passivated surfaces, which are highly active as heterogeneous catalysts for the reduction of 4-nitrophenol. The anion exchange ability of the functionalized SBA-15 was used to adsorb Au and Pd anionic complexes. The adsorbed species were then reduced and converted into supported monometallic nanoparticles or nanoalloys. Nitrogen physisorption isotherms showed that the synthetic process does not damage the mesoporous support nor block the pores. TEM/EDS and UV-vis analyses were used to prove alloy formation in the bimetallic materials through the concomitant presence of Au and Pd in the same particles and through the disappearance of the gold plasmon band as the palladium content increased. Finally, the catalytic activity of the materials increased as the palladium content increased, showing that it is possible to control the catalytic performance by tuning the material composition during the anion exchange step.